2014
DOI: 10.1542/peds.2013-4077
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Message Framing and Parents’ Intent to Immunize Their Infants for MMR

Abstract: BACKGROUND AND OBJECTIVE: Emphasizing societal benefits of vaccines has been linked to increased vaccination intentions in adults. It is unclear if this pattern holds for parents deciding whether to vaccinate their children. The objective was to determine whether emphasizing the benefits of measles-mumps-rubella (MMR) vaccination directly to the vaccine recipient or to society differentially impacts parents' vaccine intentions for their infants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 37 publications
4
59
0
1
Order By: Relevance
“…Experiences from Uganda and Peru indicated that simple messages, emphasizing health benefits to girls, were as effective in gaining high vaccination uptake as more complicated messages [59]. Similarly, simplified messages were found to increase uptake of measles, mumps, and rubella vaccination for infants [60], supporting the communications benefits of simple, clear messaging.…”
Section: Discussionmentioning
confidence: 99%
“…Experiences from Uganda and Peru indicated that simple messages, emphasizing health benefits to girls, were as effective in gaining high vaccination uptake as more complicated messages [59]. Similarly, simplified messages were found to increase uptake of measles, mumps, and rubella vaccination for infants [60], supporting the communications benefits of simple, clear messaging.…”
Section: Discussionmentioning
confidence: 99%
“…27 To support herd immunity, parents are often asked to consider wider societal interests in addition to their own child's interests. However, a review 28 found variable impacts on parents' decisions in a heterogeneous range of studies and a more recent study 29 found no additional benefit of emphasizing societal benefit over benefit to the child.…”
Section: Introductionmentioning
confidence: 99%
“…22,[25][26][27] However, published data are mixed or unclear regarding both the effectiveness of communicating to the public the societal benefits of immunization and the prevalence of free-riding among parents deciding about vaccination for their children. [28][29][30][31] Some parents do invoke the herd immunity argument as a reason not to vaccinate, suggesting that it is unnecessary that they expose their child to the risk of sideeffects from vaccination if everyone else is vaccinated to a level that prevents the spread of illnesses. 32 Parental decisionmaking about vaccination lends itself to analysis using game theory, 33 which we will not pursue here, except to support the notion suggested by Shim et al that vaccination decisions are not simply selfish or selfless but may involve complex relationships between these motivations.…”
Section: The Tragedy Of the (Herd Immunity) Commonsmentioning
confidence: 99%